1998
DOI: 10.1002/(sici)1097-4555(199808)29:8<749::aid-jrs285>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

SERS studies of electrode/electrolyte interfacial water part II—librations of water correlated to hydrogen evolution reaction

Abstract: Electrode/electrolyte interfacial water is one of the most interesting systems studied by surface-enhanced Raman spectroscopy (SERS) in the past two decades, and is brieÑy reviewed. It has been shown that the SERS characteristics of water are very di †erent from those of other surface species. Strong libration bands and the abnormal enhancement of the bending mode of water on Cu and Ag electrodes have been observed in the hydrogen evolution reaction (HER) potential region (AEÔ1.0 V SCE). The observations may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…It must be also emphasized that the effect of AgCl or Cl ions originated from the electrochemical surface roughening process on the isotopic selectivity can be ignored in the present case. This is because that the residual AgCl or adsorbed Cl anions can be completely reduced and removed at more negative region than −0.9 V [37]. In addition, we have confirmed the no effect of deposited Pt particles which are dissolved from counter Pt and redeposited on working electrode via the energy dispersive X-ray spectrometry measurements (see SI).…”
Section: Resultssupporting
confidence: 71%
“…It must be also emphasized that the effect of AgCl or Cl ions originated from the electrochemical surface roughening process on the isotopic selectivity can be ignored in the present case. This is because that the residual AgCl or adsorbed Cl anions can be completely reduced and removed at more negative region than −0.9 V [37]. In addition, we have confirmed the no effect of deposited Pt particles which are dissolved from counter Pt and redeposited on working electrode via the energy dispersive X-ray spectrometry measurements (see SI).…”
Section: Resultssupporting
confidence: 71%
“…DMSO was found to form bidentate adsorption structure on gold via Au–O and Au–S bonds by other researchers through thermal desorption spectroscopy, X-ray photoelectron spectroscopy, and scanning transmission microscopy measurements. , Overall, DMSO molecules interact with a gold substrate through Au–O bonds and Au–S bonds. A broad band was also observed at 533 cm –1 , which may be due to [Au­(OH) 2 ] − adsorbed on the gold substrate during preparation of the SERS substrate. , …”
Section: Resultsmentioning
confidence: 98%
“…21 Chen et al reported that this increase in intensity for water libration is related to the hydrogen evolution reaction. 31 They also pointed out that the increase can be attributed to the special interfacial structure of water molecules and suggested that water molecules form a structure different from that of liquid water at the electrode interface below potential zero charge. Further work is required to obtain a more exact picture of the dynamical behavior of the hydrogen evolution reaction.…”
Section: ¹1mentioning
confidence: 99%